Think-Aloud Strategy for Teaching EFL Reading - Sepri Kurniadi (Universitas Syiah Kuala, 2018)
One of the English language skills that has to be mastered by Senior High School Students in Indonesia is skill in EFL reading. This research was aimed at investigating the effectiveness of using the Think-Aloud Strategy in teaching EFL reading. It also investigated the students’ responses to the implementation of the Think-Aloud Strategy in teaching EFL reading. A quasi-experimental design with pre and post-tests was used for this research. Two classes, each with 25 second grade students from SMA Lab school in Banda Aceh were chosen as the sample for the research using a random sampling technique. The reading tests (pre and post-tests) and a questionnaire were used as the instruments for the research. The data collected was analyzed using descriptive statistics with SPSS 20.The results showed that the use of the Think-Aloud Strategy improved the experimental group (EG) students’ reading scores and then, these students also gave positive responses to the use of the strategy in teaching-learning EFL reading. Therefore, the hypothesi of this research were accepted. This means that the use of the Think Aloud Strategy significantly improved the students’ EFL reading scores as compared with those students who were taught EFL reading by using a conventional EFL reading strategy. The EG students also gave positive responses to the implementaion of the strategy in teaching EFL reading. It can be concluded that the use of this strategy significantly improved the second grade, year 11, students’ EFL reading ability.